PENGARUH SERVICE QUALITY, WEBSITE QUALITY, GOOD CORPORATE GOVERNANCE DAN TRUST PADA BEHAVIORAL INTENTION NASABAH BANK UMUM DI KOTA BATAM - Welly Sugianto (Computer Based Information System Journal, 2013)
The previous researches showed that Trust was normally influenced by the effectiveness of Good Corporate Governance Implementation, Service quality and Website Quality The previous researches examined the direct impact of Service Quality, Good Corporate Governance Implementation, Website Quality and Trust on Customer’s Behavioral Intention. Limited attention has been paid to treating those aspects as multiple and interrelated dependence relationships. This research attempts to examine how Service Quality, Good Corporate Governance Implementation, Website Quality and Trust affect Customer’s Behavioral Intention. This research uses 5 latent variables which consist of 3 exogenous constructs and 2 endogenous constructs. The impact of exogenous variables on endogenous variable was analyzed by linear regression. Results show that there are significant interrelated dependence relationships among constructs.